DEVELOPMENT TRENDS AND INVESTMENT ATTRACTIVENESS OF THE IT SECTOR OF UKRAINE - KHANENKO, Alla; KHANENKO, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the problem of investment as the most important factor in the development of the world economy, defines the leading role of investments in the effective functioning and development of the economy of any state, as well as in the activities of business entities. It is established that in the conditions of the ongoing economic crisis and military actions, there are premature  hopes for Ukrainian business lending by Western banks and companies. A new source of financing is indicated for Ukraine, which consists in attracting investments by converting Ukrainian shares into American Depository Receipts (ADRs) or Global Depository Receipts (GDRs).  The history of the development of the IT sector of Ukraine was reviewed.  The statistical data of the Ministry of Digital Transformation of Ukraine regarding the development of the country's IT companies and research were analyzed of the state of the Ukrainian IT industry according to the results of 2021, provided in the annual report of the "IT Ukraine" Association. The activity of domestic IT companies, which are in a state of active development, was considered. It was established that Ukrainian associations in the IT industry would support the formation of the domestic IT industry and the promotion of IT products to world markets: IT Ukraine, American Chamber of Commerce (ACC), European Business Association  (EBA), Union of Ukrainian Entrepreneurs (SUP), Ukrainian Venture Capital & Private Equity Association (UVCA).  The activity of IT companies during the full-scale war unleashed by Russia was reviewed.  It was established that the IT sector suffered the least losses from the war and retained 95% of the volume of orders, successfully adapting to incredibly difficult conditions. Restraining factors that stand in the way of even more rapid development of the industry have been identified: insufficient number of IT specialists;  problems with tax legislation and protection of intellectual property;  business security.The article identifies the factors that make the Ukrainian IT industry attractive to foreign investors.  Prospective areas for investment in the Ukrainian IT industry that may interest foreign investors are singled out.
Keywords: investments; IT industry; IT companies; investment attractiveness; outsourcing; freelance; startups; gadgets; cyber security; online platform; Artificial Intelligence; digitization; digital transformation